2020
DOI: 10.30659/nurscope.6.2.57-65
|View full text |Cite
|
Sign up to set email alerts
|

Dukungan sosial dan kecerdasan spiritual sebagai faktor yang memengaruhi stres Perawat di masa pandemi Covid-19

Abstract: Pendahuluan:Perawat sebagai pemberi pelayanan kesehatan dengan sifat profesinya sangat sulit untuk menghindari kontak yang erat terhadap pasiennya. Tingginya risiko keterpaparan infeksi Covid-19 serta faktor-faktor lain memengaruhi psycological well beingperawat yang berdampak pada resistensi mereka terhadap profesi. Tujuan penelitian ini untuk melihat pengaruh faktor dukungan social dan kecerdasan spiritual perawat terhadap stress. Metode: Studi ini merupakan cross sectionaldengan alat pengumpulan data menggu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
1
8
0
7
Order By: Relevance
“…Well-being has a moderate association with spiritual intelligence, which means that nurses’ well-being can be influenced by their spirituality and vice versa by the actions that they take to serve others and practice compassion. This finding validates those of other studies [ 53 , 54 , 55 ]. Spiritual and religious beliefs provide nurses with hope to consider having a peaceful life by enabling them to understand a few psychological strains placed on them and undesired occurrences that positively impact them [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Well-being has a moderate association with spiritual intelligence, which means that nurses’ well-being can be influenced by their spirituality and vice versa by the actions that they take to serve others and practice compassion. This finding validates those of other studies [ 53 , 54 , 55 ]. Spiritual and religious beliefs provide nurses with hope to consider having a peaceful life by enabling them to understand a few psychological strains placed on them and undesired occurrences that positively impact them [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…This finding aligns with a previous study that reported that nurses' stress in caring for COVID-19 patients was mild (51.8%). The Indonesian Government has established a new normal policy or adaptation of new habits for the community so that this condition may reduce the stress level of the community [25]. In addition, a study reported that less than 60% of health workers are dominated nurses who felt moderate or severe stress because there was still a fear of contracting and feeling uncomfortable when using personal protective equipment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Mengingat hal tersebut dan menimbang pandemi yang belum dapat ditentukan secara pasti kapan berakhir maka pihak manajemen perlu melakukan upaya mempertahankan kesehatan psikososial dan mental perawat. Bentuk upaya tersebut berupa support sarana dan prasarana dalam bertugas seperti APD, pelatihan management safety, prosedur pemeriksaan kesehatan, fasilitas komunikasi selama proses karantina, insentif risiko dan juga pelatihan-pelatihan manajemen stres (15).…”
Section: Gambaran Tingkat Stres Perawat Yang Terlibat Dalam Perawatan...unclassified